Factors Affecting Teamwork Effectiveness in Malaysian SMEs : Construction Industry - Yap, Wai Peng; Asokan, Vasudevan B. (INTI International University, 2020)
Teamwork is very important, but most construction companies are still in the haze of its veritable effectiveness. This study was aimed to focus on such a challenge among the SMEs in Malaysian construction industry registered under the Construction Industry Development Board grading G1 to G5. The survey based on an empirical model with four critical factors and a well-structured questionnaire was conducted. Supportive and positive results showed that: team goals and objectives, team roles and responsibilities, team shared values and team relationship are critically affecting teamwork effectiveness in the said context. The results further demonstrated that team relationship is the strongest factor affecting teamwork effectiveness based on the respondents' view. It is believed that this study could benefit the SMEs in the Malaysian construction industry in enhancing appropriate teamwork practice to improve project performance and leverage project success